2003
DOI: 10.1590/s0074-02762003000600010
|View full text |Cite
|
Sign up to set email alerts
|

Planorbidae, Lymnaeidae and Physidae of Peru (Mollusca: Basommatophora)

Abstract: In the course of several trips to Peru I had the opportunity of collecting topotypic specimens of Biomphalaria andecola (Orbigny, 1835), B. helophila (Orbigny, 1835), B. pucaraensis (Preston, 1909), Drepanotrema limayanum (Lesson, 1830), D. kermatoides (Orbigny, 1835), and Lymnaea viatrix Orbigny, 1835, besides B. tenagophila (Orbigny, 1835), Helisoma trivolvis (Say, 1817), H. duryi (Wetherby, 1879), Physa acuta Draparnaud, 1801, and seemingly P. peruviana Gray, 1828. B. pucaraensis is considered a junior syno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 5 publications
1
5
0
5
Order By: Relevance
“…The results of the present study revealed that G. pervia and B. tenagophila are closely related with high statistical support, indicating that Lymnaeidae and Planorbidae are closely related families, consistent with previous classification based on their morphological features and molecular data [45], [46]. Interestingly, MP and ML analyses revealed that families Amphibolidae and Pyramidellidae are not closely related (with very low bootstrap probability value), whereas Bayes analysis strongly supported that Amphibolidae and Pyramidellidae are closely related with high posterior probability value (Figure 3).…”
Section: Resultssupporting
confidence: 91%
“…The results of the present study revealed that G. pervia and B. tenagophila are closely related with high statistical support, indicating that Lymnaeidae and Planorbidae are closely related families, consistent with previous classification based on their morphological features and molecular data [45], [46]. Interestingly, MP and ML analyses revealed that families Amphibolidae and Pyramidellidae are not closely related (with very low bootstrap probability value), whereas Bayes analysis strongly supported that Amphibolidae and Pyramidellidae are closely related with high posterior probability value (Figure 3).…”
Section: Resultssupporting
confidence: 91%
“…Paraense (2003), however, attributed P. peruviana collected in swamps between Lima and Callao in the 1950s and 1960s to P. acuta.…”
Section: Species Discovery and Identificationmentioning
confidence: 99%
“…plicatula + + Ra. swinhoei China, Japan, Poland, Thailand, Vietnam + [ 55 ] Stagnicola palustris Italy + [ 47 ] Physidae Physa acuta Japan, Peru + [ 21 , 106 ] Planorbidae Biomphalaria alexandrina Egypt, Libya, Sudan + [ 24 ] Bio. amazonica + …”
Section: Introductionmentioning
confidence: 99%
“…glabrata Caribbean Islands, south America + [ 24 ] Bio. helophila Cuba, Peru + + [ 28 , 106 ] Bio. intermedia + Bio.…”
Section: Introductionmentioning
confidence: 99%